(untitled) (Revista Dialectus - Revista de Filosofia, 2020)
Hegel and Marx share the concept of a strict deduction of the genesis of forms—forms of thought and being in the case of Hegel, and economic forms in the case of Marx: "the form of commodity, the form of money, the form of capital, the form of profit, of interest, etc." (Reichelt) This article demonstrates that Kozo Uno and Thomas T. Sekine in Japan, as well as Hans-Georg Backhaus and Helmut Reichelt in Germany, independently discovered "the premature and unnecessary reference to the labour theory of value in the early part of Capital" (Uno), stating that Marx contradicts his own method by establishing that socially necessary labor constitutes the substance of value right at the very beginning of Capital—in the sphere of circulation—although necessary prerequisites, such as competition, are only available later—in the sphere of production. Finally, Uno’s and Sekine’s theory of capital is integrated into a system in accordance with Hegel’s encyclopedia, involving Hegel’s Logic (as logic), Uno’s/Sekine’s notion of capital (based on Marx) as base/substructure (nature), and a superstructure (spirit).